2011
DOI: 10.1007/s10735-011-9328-4
|View full text |Cite
|
Sign up to set email alerts
|

The expression of Akt and ERK1/2 proteins decreased in dexamethasone-induced intrauterine growth restricted rat placental development

Abstract: The placenta is a complicated tissue that lies between maternal and fetal compartments. Although the architecture of the human and rodent placentas differ a little in their details, their overall structures and the molecular mechanisms of placental developments are thought to be very similar. In rats, fetal-placental exposure to maternally administered glucocorticoids decreases birth weight and placental weight. The mechanism underlying the placental growth inhibitory effects of glucocorticoids have not been e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 56 publications
2
18
0
Order By: Relevance
“…In our previous study, we have shown that p-Akt expression was decreased in placentas of DEX treated rats (Ozmen et al, 2011). With our recent study we have both confirmed our previous results and also observed that not only Akt activation but also p70S6K and 4EBP1 activations were decreased by glucocorticoid overexposure.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In our previous study, we have shown that p-Akt expression was decreased in placentas of DEX treated rats (Ozmen et al, 2011). With our recent study we have both confirmed our previous results and also observed that not only Akt activation but also p70S6K and 4EBP1 activations were decreased by glucocorticoid overexposure.…”
Section: Discussionsupporting
confidence: 89%
“…Control and IUGR groups were generated as previously described (Ozmen et al, 2011). IUGR-inducing dosages of Dexamethasone 21-acetate (Sigma) in rats were selected as previously demonstrated (Benediktsson et al, 1993).…”
Section: Animals and Tissue Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…The decrease in ERK1/2 and Akt activation may result in cell survival inhibition or apoptosis stimulation. Consequently, Dex induced placental and embryonal developmental abnormalities could be associated with reduction of Akt and ERK1/2 activation [91]. In another study, decreased levels of placental Akt phosphorylation was observed after in utero exposure to Dex [92].…”
Section: The Effects Of Glucocorticoids On Placental Cell Cyclementioning
confidence: 94%
“…HUVECs were cultured at different concentrations (0. In another study of ours, we investigated the effects of glucocorticoids on rat placental development depending on the PI3K/Akt and MAPK-ERK1/2 pathways [91]. It was observed that, the IUGR group had significantly smaller embryos on day 20 of gestation and had smaller placentas on day 14, 16, 18 and 20 compared with control.…”
Section: The Effects Of Glucocorticoids On Fetal and Placental Angiogmentioning
confidence: 97%